Activation of human ether-a-go-go related gene (hERG) potassium channels by small molecules - Zhou Ping-zheng; Babcock Joseph; Liu Lian-qing; Li Min; Gao Zhao-bing (Acta Pharmacologica Sinica, 2016)
Human ether-a-go-go related gene (hERG) potassium (K+) channels play a critical role in cardiac action potential repolarization. Mutations that reduce hERG conductance or surface expression may cause congenital long QT syndrome (LQTS). However, the channels can be inhibited by structurally diverse small molecules, resulting in an acquired form of LQTS. Consequently, small molecules that increase the hERG current may be of value for treatment for LQTS. So far, nine hERG activators have been reported. The aim of this review is to discuss recent advances concerning the identification and action mechanism of hERG activators.